Ionically and covalently crosslinked hydrogel particles based on chitosan and poly(ethylene glycol) - Popadyuk, Nadiya; Zholobko, Oksana; Donchak, Volodymyr; Harhay, Khrystyna; Budishevska, Olha; Voronov, Andriy; Kohut, Ananiy; Voronov, Stanislav (Publishing House of Lviv Polytechnic National University, 2014)
Self-assembled pH-sensitive reactive submicron-sized particles have been developed via intermolecular electrostatic interactions between chitosan and a carboxylated oligoperoxide having poly(ethylene glycol) fragments. The particles have the structure of an ionically crosslinked hydrogel and their size and surface charge depend on the conditions of their formation (i.e., pH and the functional group ratio). The presence of peroxide groups in the oligoperoxide has enabled to synthesize covalently crosslinked pH-sensitive particles. Електростатичною міжмолекулярною взаємодією хітозану та карбоксиловмісного олігопероксиду з фрагментами поліетиленгліколю одержані самовпорядковані рН-чутливі реакційноздатні субмікронні частинки, які мають структуру йонно-зшитого гідрогелю, а їх розмір та поверхневий заряд залежить від умов формування (рН і співвідношення функціональних груп). Наявність пероксидних груп у складі олігопероксиду дала можливість одержати ковалентно зшиті рН-чутливі частинки.
Йонно і ковалентно зшиті гідрогелеві частинки на основі хітозану полетиленгліколю
Keywords: hydrogel particles; pH-sensitive particles; self-assembly; oligoperoxide; chitosan; гідрогелеві частинки; pH-чутливі частинки; самоорганізація; олігопероксид; хітозан